Analytical approximation of surface potential and analysis of C–V characteristics of bulk MOSFETs at cryogenic temperatures. (November 2022) - Manzoor, Wajid; Dutta, Aloke K.; Chauhan, Yogesh Singh
Abstract: In this paper, we present an accurate analytical approximation of the surface potential for bulk MOSFETs, starting from its transcendental relation with respect to the gate voltage, valid from room temperature to deep cryogenic temperatures, encompassing the entire operating region. The results obtained from the proposed analytical model for the surface potential have very high accuracy, with the maximum absolute error of the order of nanovolts, when compared with the results of numerical calculations. We also investigate and present the temperature dependence of the semiconductor charge density and its physical implications on the C–V characteristics. A kink is observed in the C–V characteristics near flatband, due to dopant freeze-out at cryogenic temperatures. We have also been able to develop a model for the C–V characteristics, that captures this kink accurately, over a wide temperature range. The results obtained from this model are compared with both TCAD simulations as well as with experimental data, and the match is found to be excellent.